2002
DOI: 10.2466/pr0.2002.90.2.677
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Estimates of Return Rates as a Measure of Public Attitudes to Violence

Abstract: An analysis of letters placed in Mobile, Alabama and Sioux Falls, South Dakota (ns = 500 and 600) showed return rates among the several addresses were essentially uncorrelated (rs = -.11 to .08) so interpoll reliability is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Such strategies include using first-class postage on outgoing and return envelopes (Yammarino, Skinner, & Childers, 1991), using hand-signed cover letters (Dodd, Bowell, & Litwin, 1988), using colored paper for surveys (Fox, Crask, & Kim, 1988), conducting follow-up mailings (Ramsdell, 1995), using surveys that are four pages or less (Roszkowski, 1990), and placing demographic questions at the end of the survey (Roberson & Sundstrom, 1990). In addition, other studies have identified effective strategies to address the return of lost letters (Bridges & Clark, 2000;Bridges, Ryan, & Scheibe, 2000;Bridges, Scheibe, & Meyer, 2002). Several additional techniques have also been noted in enhancing response rates from Dillman's total design method (Dillman, 1978;Salant & Dillman, 1994;Dillman, Smyth, & Christian, 2008).…”
mentioning
confidence: 92%
“…Such strategies include using first-class postage on outgoing and return envelopes (Yammarino, Skinner, & Childers, 1991), using hand-signed cover letters (Dodd, Bowell, & Litwin, 1988), using colored paper for surveys (Fox, Crask, & Kim, 1988), conducting follow-up mailings (Ramsdell, 1995), using surveys that are four pages or less (Roszkowski, 1990), and placing demographic questions at the end of the survey (Roberson & Sundstrom, 1990). In addition, other studies have identified effective strategies to address the return of lost letters (Bridges & Clark, 2000;Bridges, Ryan, & Scheibe, 2000;Bridges, Scheibe, & Meyer, 2002). Several additional techniques have also been noted in enhancing response rates from Dillman's total design method (Dillman, 1978;Salant & Dillman, 1994;Dillman, Smyth, & Christian, 2008).…”
mentioning
confidence: 92%